Metodologi Hukum Islam Abd al-Ḥalīm Maḥmūd - M. Lathoif Ghozali (Islamica: Jurnal Studi Keislaman, 2014)
This article discusses the concept of ijtihād (legal reasoning) and the typology of legal thought of Abd al-Ḥalīm Maḥmūd. According to Maḥmūd, ijtihad is devoting all abilities of a mujtahid to arrive at the essence and substance of a problem intended by the Prophet Muhammad. This definition is supported by the division of ijtihād into two: ijtihād istinbāṭī, the object of which is the texts of the Qur'ān or the Sunnah, and ijtihād taṭbīqī, the object of which is legal problems of the time. Mahmud maintains that a mujtahid should meet certain qualifications such as the abilities of understanding Arabic language, memorizing the Qur'ān, understanding asbāb al-nuzūl (causes of revelation), memorizing the Traditions of the Prophet related to legal matters, and the brilliance in making legal reasoning and conclusions. Maḥmūd belongs to moderate group that agrees with the formalization of private laws, while public laws in his view serve only as materials for national laws. Maḥmūd also gives an emphasis on the integration between naṣṣ (text) and maqāṣid al-sharī'ah (the objectives of law).